The Content of Teaching Foreign Languages - Bakirova Hilola Botiraliyevna (Genius Journals, 2021)
The article examines the content of teaching foreign languages as intermediate skills, language skills, texts in graphic and sound design, themes and situations within which speech skills are formed, language concepts that are absent in the native language of students. The concept of the content of teaching a foreign language is revealed, different approaches and points of view of researchers are analyzed. On the basis of general didactic concepts of the content of education, the specificity of the content of teaching a foreign language at a university is shown and an analysis of its components is carried out.
Keywords: Learning content; language skills; speech skills; language concepts